A New Multifunctional TriazineCarbazole Compound with High Triplet Energy for High‐Performance Blue Fluorescence, Green and Red Phosphorescent Host, and Hybrid White Organic Light‐Emitting Diodes. Issue 7 (23rd May 2014) - Liu, Xiao‐Ke; Zheng, Cai‐Jun; Xiao, Jing; Lo, Ming‐Fai; Chen, Zhan; Lee, Chun‐Sing; Liu, Chuan‐Lin; Ou, Xue‐Mei; Li, Fan; Zhang, Xiao‐Hong
Abstract A blue fluorescent compound, 9‐[4‐(4, 6‐diphenoxy‐1, 3, 5‐triazin‐2‐yl)phenyl]‐9H‐carbazole (POTC), the triplet energy level of which reaches 2.76 eV, has been designed and synthesized. POTC is an excellent blue emitter as well as host for green and red phosphors, and therefore, matches the requirements of the host for single‐emitting‐layer fluorescence and phosphorescence hybrid white organic light‐emitting diodes (OLEDs). The blue, green, red, and white devices based on POTC show maximum external quantum efficiencies (EQEs) of 2.4, 22.4, 13.0, and 8.1 %, respectively. Even at a high brightness of 1000 cd m−2, these values maintain EQEs of 2.3, 22.1, 11.1, and 7.0 %, respectively, indicating less than 15 % roll‐offs from the maxima.